Netz, Reviel (2013). Alambre de púas: una ecología de la modernidad - Sastre Juan, Jaume (Documents d’Anàlisi Geogràfica, 2014)
NETZ, Reviel (2013) Alambre de púas: una ecología de la modernidad Buenos Aires: Eudeba, 258 p. ISBN 978-950-23-2116-5